Prática pedagógica aos educandos com deficiência intelectual numa escola de ensino fundamental com alto IDEB - Porta, Wilma Carin Silva (2015)
In the current context of inclusive education, in which students with intellectual disability (ID) constitute the largest group among all the deficiencies , questions about the performance of the teachers of the regular classrooms with high Index of Basic Education Development (IDEB) to these students are important. The present study aimed to analyze the potential and limits of pedagogical practice of elementary school teachers of the first cycle (from the first grade to the fifth) who work with students with intellectual disability in a public school with high IDEB. This is a field research with a qualitative approach and descriptive design. The study was conducted in a elementary school in the countryside of São Paulo, and included the participation of three regular school teachers that had students with intellectual disability in their classroom. The tools for data collection were: script observation, semistructured interviews and field journal; being the data collection based in the observation of the everyday school life of students with intellectual disability and in the recorded interviews, that were previously scheduled and happened individually. The processes after data collection were organization of the observation records and field journal, and transcription of the audio interviews. For the treatment of the data, we classified the elements into categories and put in evidence the highlighted elements in each proposed item in the scripts (observation and semistructured interviews) in order to build the analytical categories. The data revealed the complexity of the process of School Inclusion, particularly in the ambit of pedagogical practices directed at teaching and learning processes of students with intellectual disability, and showed that the school faces many obstacles so that it can adequately serve those students. It was noticed that even in a school with high Ideb the process of inclusion of students with ID presented attitudinal, pedagogical and training gaps still to be overcomed. In summary, the data revealed the presence of traditional teaching practices with learners with ID, the mere transmission of the contents centered on the teacher's figure; whereas students with intellectual disability have specific and pedagogical demands that are not satisfied with this practice; although. With respect to observed demands, the teachers identified the need for continuing education on specific contents of special education and Curricular Adequacy; and the participation of the families of these students and the partnership with a special education teacher. We hope that this research contributes with the discussion and understanding of the pedagogical practice with students with intellectual disability as well as on the problems and demands of the public school regarding the inclusion of these students.